2015
DOI: 10.1039/c5ra12776a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-microbial efficiency of nano silver–silica modified geopolymer mortar for eco-friendly green construction technology

Abstract: 24A silver-silica nano composite based geopolymer mortar has been developed by 25 simple adsorption of silver in a suitable amount of colloidal silica suspension for anti-26 bacterial property development. The silver nanoparticles (3-7 nm) were attached on the 27 surface of 20-50 nm sized silica nanoparticle. The silver-silica nano-composite was 28 characterized by Transmission Electron Microscope (TEM), X-Ray Diffraction (XRD) and 29 Energy Dispersive X-ray Spectral analysis. Mechanical strength, durabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…AAMs have many potential applications in water and wastewater treatment, including adsorbents/ion-exchangers, membranes and filtration media, photocatalysts, and solidification/stabilization of water and wastewater treatment residues. In addition, they can be used as antibacterial materials after the incorporation of copper (Hashimoto et al 2015) or silver (O'Connor et al 2010) through ion exchange or addition of nanoparticles (such as silver silica nanocomposites) into the aluminosilicate matrix of AAMs (Adak et al 2015). Although the aforementioned examples were intended as antimicrobial binders, there are numerous examples with similarly modified zeolites to indicate potential applicability for disinfection of wastewaters or groundwater (Akhigbe et al 2014;De la Rosa-Gómez et al 2008a, b;Dolic et al 2015;Mpenyana-Monyatsi et al 2012;Johari et al 2016).…”
Section: Applications In Water and Wastewater Treatmentmentioning
confidence: 99%
“…AAMs have many potential applications in water and wastewater treatment, including adsorbents/ion-exchangers, membranes and filtration media, photocatalysts, and solidification/stabilization of water and wastewater treatment residues. In addition, they can be used as antibacterial materials after the incorporation of copper (Hashimoto et al 2015) or silver (O'Connor et al 2010) through ion exchange or addition of nanoparticles (such as silver silica nanocomposites) into the aluminosilicate matrix of AAMs (Adak et al 2015). Although the aforementioned examples were intended as antimicrobial binders, there are numerous examples with similarly modified zeolites to indicate potential applicability for disinfection of wastewaters or groundwater (Akhigbe et al 2014;De la Rosa-Gómez et al 2008a, b;Dolic et al 2015;Mpenyana-Monyatsi et al 2012;Johari et al 2016).…”
Section: Applications In Water and Wastewater Treatmentmentioning
confidence: 99%
“…In addition, the increase in alkali content from 35-45% of the total binder decreases the compressive strength of samples [53]. Likewise, the inclusion of nanoparticles enhances the compressive strength of geopolymer mortar at different curing age [136]. From Table 5, it is concluded that the strength development of FA-based GPC at ambient temperature enhanced due to the addition of external agents like superplasticizers or additives.…”
Section: Compressive Strengthmentioning
confidence: 95%
“…In addition, the increase in alkali content from 35-45% of the total binder decreases the compressive strength of samples [53]. Likewise, the inclusion of nanoparticles enhances the compressive strength of geopolymer mortar at different curing age [136].…”
Section: Compressive Strengthmentioning
confidence: 97%
“…Hence, it is of great research interest to examine IPs composites with embedded -NPs as antimicrobial agents. The addition of nanosilver improved the mechanical strength, durability, and antibacterial properties of Ag-IPs composites [40][41][42]. Additionally, CuO and ZnO NPs can be included as reinforcement for IPs pastes [43,44] and also, generating antibacterial IPs surfaces [45,46].…”
Section: Introductionmentioning
confidence: 99%